A Study on Knowledge, Attitude, and Practice of Standard Precautions andPost-Exposure Prophylaxis for HIV/Aids Among Healthcare Professionals inTertiary Care Hospital, Shivamogga - Chandana M; Praveen Kumar N; Avinash Patil; Raghavendraswamy Koppad; Aseeba O P K (RGUHS Journal of Medical Sciences)
Background Standard precautions and post-exposure prophylaxis PEP are proven ways of protecting healthcare professionals from the risk of acquiring blood-borne infections through occupational exposure. Medical interns are vulnerable to these risks due to their limited experience and clinical exposure.AimsObjectives This study aims to evaluate medical interns knowledge and practice of standard precautions identify any gaps between knowledge and practice and assess their knowledge attitude and practice regarding post-exposure prophylaxis PEP guidelines for HIV.Methods Data were collected from 119 interns using a pretested self-administered questionnaire. The collected data was entered and analyzed using MS Excel.Results Among the 119 interns 115 96.64 were aware of proper handwashing practices but only 98 82.35 followed them correctly. Additionally 45 37.82 interns reported recapping or bending syringes at the workplace. A total of 33 27.73 interns had occupational exposure to HIV-risk conditions and among those prescribed post-exposure prophylaxis PEP 16 out of 24 66.67 completed the regimen.Conclusions The study identifies a significant knowledge and practice gap among medical interns about standard precautions SP. Despite having inadequate knowledge and poor practice of SP and PEP guidelines most interns have a favourable attitude toward PEP. These findings highlight the potential for improvement through training and continuous monitoring of SP and PEP guidelines offering a hopeful outlook for the future of healthcare practices.